2022
DOI: 10.1038/s41531-022-00327-6
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics synergized with conventional regimen in managing Parkinson’s disease

Abstract: Parkinson’s disease (PD) is mainly managed by pharmacological therapy (e.g., Benserazide and dopamine agonists). However, prolonged use of these drugs would gradually diminish their dopaminergic effect. Gut dysbiosis was observed in some patients with PD, suggesting close association between the gut microbiome and PD. Probiotics modulate the host’s gut microbiota beneficially. A 3-month randomized, double-blind, placebo-controlled clinical trial was conducted to investigate the beneficial effect of probiotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 89 publications
3
73
0
Order By: Relevance
“…Sampson et al found that the motor impairment of germ-free PD-like mice worsened when they were administered the gut microbiota of patients with PD, demonstrating the role of gut microbes and short chain fatty acids (SCFAs) in α-synuclein-induced neurotoxicity and inflammation [ 10 ]. By transplanting the microbiota of young healthy mice into older PD mice, Marcus et al showed that the age-related cognitive and behavioral impairments could be corrected, in part through altering the synthesis of SCFA and neurotransmitters [ 11 ]. The results of these studies indicate that one of the major contributors to PD is an imbalance of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Sampson et al found that the motor impairment of germ-free PD-like mice worsened when they were administered the gut microbiota of patients with PD, demonstrating the role of gut microbes and short chain fatty acids (SCFAs) in α-synuclein-induced neurotoxicity and inflammation [ 10 ]. By transplanting the microbiota of young healthy mice into older PD mice, Marcus et al showed that the age-related cognitive and behavioral impairments could be corrected, in part through altering the synthesis of SCFA and neurotransmitters [ 11 ]. The results of these studies indicate that one of the major contributors to PD is an imbalance of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Limited in vitro experiments have been carried out to evaluate the possible beneficial and neuroprotective effects of probiotics in alleviating the typical features of PD ( Table 1 ) [ 325 , 328 , 329 , 330 , 331 , 332 , 333 , 334 , 335 , 336 , 337 , 338 , 339 , 340 , 341 , 342 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Therapeutic Approachesmentioning
confidence: 99%
“…Finally, another randomized, double-blind, placebo-controlled clinical trial, performed by using the probiotic strain Probio-M8 ( B. animalis subsp. lactis Probio M-8), together with conventional drugs (benserazide and dopamine agonists), showed amelioration in sleep quality, cognitive dysfunction, defecation, and attenuation of GI symptoms [ 342 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Therapeutic Approachesmentioning
confidence: 99%
“…Promising evidence includes probiotic mediated increases in dopamine [ 16 ], as well as its metabolites, including 3,4-Dihydroxyphenylacetic acid (DOPAC) and Homovanillic acid (HVA) [ 17 ]. Further, probiotics are shown to increase other aspects of neurodegenerative disease, such as improvements in sleep quality, alleviation of anxiety, gastrointestinal symptoms, reduction of oxidative stress and anti-inflammatory effects [ 18 , 19 ]. However, other therapeutic modalities have also been implicated in this regard, although not currently as utilized in practice when compared to probiotics in the context of restoring dopaminergic deficits in neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%